Coaches leadership styles as preferred by different gender among Sukma Johor athletes / Mohamad Amir Aizat Bahruddin - Bahruddin, Mohamad Amir Aizat (Faculty of Sport Science and Recreation, 2015)
Coaches' leadership style and coaching behavior is the style used by the coach as a leader for the team and the organization. There are various of style that can be used by the leader as long as it is suit with the team and in which the team can achieve high performance in the sports. The study was conducted on two group samples which is male (N =75) and female (N =75) athletes which total (N =150) are participated in SUKMA event. Purposes of this study were to identify the coaches' leadership style as preferred by different gender among SUKMA Johor athletes. To collect data from subjects, the Leadership Scale for Sport (LSS) were used to examined style of coaching leadership that is preferred. Questionnaire distributed to athletes that are including a five factor solution with 40 items describing the most preferred dimension of coaching leadership was selected as the most meaningful These factors were named Training and Instruction, Democratic Behavior, Autocratic Behavior, Social Support, and Positive Feedback. Male athletes more preferred the training and instruction coaching behavior which mean score 4.48±O.12 and female are more preferred autocratic behavior which mean score 4.68±1.24.